The Links Between Learning Objectives, Sociodemographic Factors and Learning Achievement Among Participants of a Professional Development MOOC - Njingang Mbadjoin, Théodore; Chaker, Rawad (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
This article explores the success factors in a professional Massive Open Online Course (MOOC). On the one hand, we are investigating whether professional goals, success goals, and certification goals are linked to success. On the other hand, we seek to verify whether socio-professional, demographic factors or the time available for training are also linked to success. Our results show that external factors such as gender, occupational group, being employed or not, and availability influence success in continuing online education, rather than conative factors related to professional and learning goals. These results underline the importance of ecological elements in the educational accomplishment in a training situation.